The relationship between knowledge, self-efficacy and nursing spiritual care behaviors in school-age children in pediatric room - Madu, Yunita Gabriela; Lely Lusmilasari; Sri Hartini; Mery Solon; Wirmando, Wirmando; Bakri, Asrijal; Paseno, Matilda Martha; Linggi, Elmiana Bongga (Universitas Airlangga, 2023)
Introduction: Spiritual care for children is important in the care provided by nurses so that children do not feel guilty when being treated in the hospital. It is important for nurses to understand that the process of providing nursing care is bio-psycho-social and spiritual based. This study aimed to find out the relationship between knowledge, self-efficacy, and nurse behavior in the provision of spiritual care for school-age children in hospitals. Methods: This study used a cross-sectional approach with a purposive sampling technique followed by 102 nurses who cared for school-age children in a pediatric nursing room. Knowledge was measured using the Spiritual Care-Giving Scale, Self-Efficacy was measured by Burkhart Spiritual Care Inventory (BCI), and Nurse Spiritual Care Therapeutic Scale (NSCTS) to measure behavior. The data were analyzed using the Kolmogorov-Smirnov test, and Spearman correlation test. Results: There was no significant correlation between knowledge and behavior (p = 0.181; r = 0.133); however, there was a significant correlation of nurse behavior with self-efficacy (p = 0.027; r = 0.219), age (p = 0.015; r = 0.240), length of work (p = 0.021; r = 0.228), and spiritual care training (p = 0.001). Conclusion: Knowledge does not have a significant relationship with behavior. However self-efficacy, age, length of work, and spiritual care training significantly affects the nurse's behavior in providing spiritual care to school-age children in the hospital.